Strategi Akademik untuk Penyelesaian Studi Tepat Waktu: Pembekalan Mahasiswa Penerima KIP-K di Universitas Teuku Umar - Budianto, Budianto; Fauzi, Ahmad; Sunandar, Suci (LPMP Imperium, 2026)
Students receiving the Indonesia Smart Card for College (KIP-K) are required to maintain academic performance and complete their studies on time. However, challenges such as poor time management, low learning motivation, and limited communication with academic supervisors often hinder academic success. This community service activity aimed to provide academic guidance for first-semester female KIP-K students residing in the Student Dormitory at Universitas Teuku Umar to support timely graduation and maintain a minimum GPA of 3.00. The activity was conducted through lectures and interactive discussions involving 70 students from various study programs and regions. The results showed high participant enthusiasm, reflected in active discussions covering learning strategies, time management, academic integrity, communication ethics with lecturers, organizational balance, and the use of Artificial Intelligence (AI) in academic tasks. Furthermore, the activity improved participants’ understanding of effective learning strategies, academic motivation, and personal responsibility. This program contributed to strengthening students’ academic preparedness, character development, and awareness of academic ethics among KIP-K scholarship recipients.